Sensory Properties and Consumer Liking of Buffalo Stracchino Cheese - Di Cairano, M.; Pacelli, C.; Bragaglio, A.; Napolitano, F.; Braghieri, A. (Journal of Buffalo Science, 2021)
The present study aims to characterize buffalo Stracchino cheese (BS) from a sensory point of view and verify how much consumers like it compared with the standard Stracchino cheese obtained from cow milk (CS). Nine panelists specifically trained to evaluate Stracchino cheese were used to conduct a quantitative descriptive sensory analysis, whereas 80 untrained consumers balanced for gender participated in the hedonic consumer test. Stracchino appearance was affected by milk type with higher intensities perceived for BS in terms of whiteness (P<0.0001) and shininess (P<0.001). As to taste and texture, BS showed higher sourness and oiliness intensities than CS, respectively (P<0.0001). Milk type did not affect the overall liking or the liking in terms of taste/flavor, texture, and appearance, but consumers rated both products at scores well above the neutral point. In addition, the liking expressed in blind conditions (i.e., without information on the milk type) was significantly lower as compared with the liking elicited by the expectations (i.e., based only on the information on the milk type) (P<0.05 and P<0.10, for CS and BS, respectively). We conclude that the good eating quality of buffalo Stracchino cheese as assessed by the consumer panel and the lack of differences between CS and BS in terms of a consumer may anticipate a possible good positioning of this novel product in the market of fresh cheese.